2013
DOI: 10.1055/s-0033-1335843
|View full text |Cite
|
Sign up to set email alerts
|

Ultraschall Emissionen: Thermische (TI) und mechanische (MI) Indizes

Abstract: Link to publication Citation for published version (APA): Kollmann, C., ter Haar, G., Dolezal, L., Hennerici, M., Salvesen, K. A., & Valentin, L. (2013). Ultrasound Output: Thermal (TI) and Mechanical (MI) Indices. Ultraschall in der Medizin, 34(5), 422-434. DOI: 10.1055/s-0033-1335843 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…Thermal effect is another important effect induced by ultrasound, and previous literature has reported that elevated temperature can induce tumor death or apoptosis [35] . Thermal effect is related to the intensity of ultrasound and the Thermischer Index (TI) [36] . In this study, the acoustic power of the US instrument was less than 720 mW/cm 2 and TI was approximately 0.1.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal effect is another important effect induced by ultrasound, and previous literature has reported that elevated temperature can induce tumor death or apoptosis [35] . Thermal effect is related to the intensity of ultrasound and the Thermischer Index (TI) [36] . In this study, the acoustic power of the US instrument was less than 720 mW/cm 2 and TI was approximately 0.1.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, the FDA has formulated two criteria to quantify the tissue effects induced by US, namely thermal index (TI) and mechanical index (MI). [ 135 ] The former represents the energy required to raise the tissue temperature by 1 °C, while the latter refers to a combination of ultrasonic parameters such as frequency and amplitude. On these grounds, current efforts should focus on the widespread use of US with high frequency, low amplitude, short irradiation time, and few duty cycles to achieve drug release and drug activity safely.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…A lower MI indicates a lower degree of cavitation effect. A value lower than 0.5 is considered to indicate no bubble growth [37,38], whereas 1.9 is considered to be the maximal threshold of no bioeffects, which is a value that is also adopted by the Food and Drug administration in its regulation for diagnostic ultrasound [37]. In regular HIFU treatment for cancers, which utilizes a high intensity of ultrasound, the cavitation effect plays an important role in curing lesions.…”
Section: Mechanical Effectsmentioning
confidence: 99%